ANALISIS TINGKAT PELAYANAN PENUMPANG TERMINAL DOMESTIK DAN INTERNASIONAL BANDARA INTERNASIONAL ADISUTJIPTO YOGYAKARTA - , RIO NENDRA PURWA P. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The passenger terminal of airport plays an important role in the system, ie to the place where the activities of passenger departure and arrival processing takes place, but it also serves to meet the various needs of passengers and goods, ranging from check-in until the arrival hall. PT. Angkasa Pura I (Persero) Adisutjipto Yogyakarta airport by number of passengers in 2013 reached 6 million passengers already exceeds the current capacity of 1.5 million passengers. Overall width Adisucipto Airport terminal currently is 9.201 m2, with an area of 7.609 m2 domestic terminal and an international terminal area of 1.071 m2, it does not meet the standards SKEP 77-VI- 2005 on standard airport terminal. The results of the analysis of the level of passenger service that has been done shows at the international terminal to meet the minimum standard is 3.175,975 m2 area, then redesign the international terminal will be moved to a new building with an area of 4.950 m2 that can meet those standards. At the domestic terminal to meet the minimum standards that a broad area of 13.257.,15 m2, while the expansion of the planned use of the existing international terminal building just reached 8.680 m2 case This is caused by limited land, so that the expansion is done only to reduce congestion at the domestic departure lounge only. Limited land a major obstacle in the redesign of the terminal, in other words until the expansion can not meet the standards SKEP 77-VI-2005, but only to reduce the existing level of density. In order to meet these standards then Adisutjipto Yogyakarta airport should be moved and built a new airport.